ISYARAT DAN MANIFESTASI SENI DALAM AL-QUR’AN: SATU SOROTAN - Harun, Makmur; Yusof, Abdullah (Journal of Al-Tamaddun, 2009)
Al-Qur’an contains arts literature, full of meanings, has various arts of calligraphy, asking humankind to learn continously, read and write despite of asking people to enjoin good and prevent evil. Apart of being sources in various aspects, al-Qur’an has discusses arts in details, as a manifestation to the world, science, literature, culture, which its writing has become the medium of dakwah, artistic, esthetic and as a way of life in shaping symbols of art which influence human internal and external life. This paper will attempt to discuss the beauty of arts in the Qur’an in its various shape and meaning in order to learn from its spiritual or esthetical symbols of life as individual or society.